Eco-Extraction of Essential Oil of the Species Salvia Officinalis L. Systematic Characterization and Parametric Modeling - DJERMANE Mohamed; Abidi Abdenabi; Cheraif Imed; Toubal Abdelaziz; Noureddine Gherraf (EURESIAN PUBLICATIONS, 2018)
In this study, the response surface methodology (RSM) was used to optimize the hydrodistillation process of Algerian Salvia officinalis essential oil. The effects of grain size, condensing flow rate and extraction time on oil yield were studied. A 3-factor design by the BoxBehnken method was used to produce factor combinations, from the response surface analysis. A second-order polynomial expression was deduced and used to determine the best yield efficiency of extracted oil according to the optimal conditions. Analysis of variance (ANOVA) indicates that the generated second-order polynomial model was highly significant with R2 = 0.9589 and P <0.006. Optimum oil yield conditions (0.98%) were estimated at a particle diameter of 2mm, a condensation flow rate of 1.4mL/min of and an extraction time of 210min. The essential oil extracted from the sage leaves by hydrodistillation was analyzed by GC/MS, to afford α.-Thujone, camphor, 1,8- cineole and β.-Thujone as main components.